Hubungan antara Job Insecurity dengan Work Engagement Karyawan Bank Y - Naurah Aninda; Muhammad Ilmi Hatta (UNISBA Press, 2024)
Abstract. This study discusses the relationship between job insecurity and work engagement among employees of Bank Y. Organizations need dynamic and dedicated employees, namely employees who have engagement in carrying out their work [2]. Job insecurity can reduce work engagement and performance, thus highlighting the need for strategies to reduce job insecurity and increase work engagement. Work engagement is very important for employee performance and well-being. The Job demands-Resources (JD-R) theory is relevant to work engagement because both aspects can determine the level of work engagement. Although job insecurity can affect work engagement, this relationship is complex and requires further research. The research method used in this study is quantitative with a correlation research design. The measuring instrument for job insecurity uses the Job insecurity Scale, and for work engagement uses the UWES-9 measuring instrument. And the results of the Pearson Correlation Output between the Job insecurity and Work engagement variables are known to have a correlation value of 0.033, this value is too close to 0 which can be interpreted that there is a very weak linear relationship between the two variables. Abstrak. Penelitian ini membahas mengenai hubungan antara job insecurity dan work engagement di kalangan karyawan bank Y. Organisasi membutuhkan karyawan yang dinamis dan berdedikasi, yaitu karyawan yang memiliki engagement dalam menjalankan pekerjaannya [2]. Job insecurity dapat mengurangi work engagement dan kinerja, sehingga menyoroti perlunya strategi untuk mengurangi job insecurity dan meningkatkan work engagement. Work engagement sangat penting untuk kinerja dan kesejahteraan karyawan. Teori Job demands-Resources (JD-R) relevan dengan work engagement karena kedua aspek tersebut bisa menentukan tinggi rendahnya work engagement. Meskipun job insecurity dapat mempengaruhi work engagement, hubungan ini kompleks dan membutuhkan penelitian lebih lanjut. Metode penelitian yang digunakan dalam penelitian ini adalah kuantitatif dengan desain penelitian korelasi. Alat ukur untuk job insecurity menggunakan Job insecurity Scale, dan untuk work engagement menggunakan alat ukur UWES-9. Dan didapatkan hasil Output Korelasi Pearson antara variabel Job insecurity dan Work engagement diketahui memiliki nilai korelasi 0.033, nilai ini terlalu dekat dengan 0 yang dapat diartikan bahwa terdapat hubungan linear yang sangat lemah diantara kedua variabel.